GSK-3beta controls osteogenesis through regulating Runx2 activity. - Fumitaka Kugimiya; Hiroshi Kawaguchi; Shinsuke Ohba; Naohiro Kawamura; Makoto Hirata; Hirotaka Chikuda; Yoshiaki Azuma; James R Woodgett; Kozo Nakamura; Ung-il Chung (PLoS ONE)
Despite accumulated knowledge of various signalings regulating bone formation, the molecular network has not been clarified sufficiently to lead to clinical application. Here we show that heterozygous glycogen synthase kinase-3beta (GSK-3beta)-deficient mice displayed an increased bone formation due to an enhanced transcriptional activity of Runx2 by suppressing the inhibitory phosphorylation at a specific site. The cleidocranial dysplasia in heterozygous Runx2-deficient mice was significantly rescued by the genetic insufficiency of GSK-3beta or the oral administration of lithium chloride, a selective inhibitor of GSK-3beta. These results establish GSK-3beta as a key attenuator of Runx2 activity in bone formation and as a potential molecular target for clinical treatment of bone catabolic disorders like cleidocranial dysplasia.